The effect of human capital on organizational readiness: An analytical study at the Middle Technical University - Wahhab Alyasiri , Weam; Hassoun Al-Taee , Ali (Journal of Economics and Administrative Sciences, 2024)
The study seeks to assess how human capital, encompassing aspects like knowledge, skills, experience, and abilities, impacts the attainment of organizational readiness across cognitive, emotional, and behavioral dimensions at Central Technical University. The problem of the study begins by addressing the basic question of revealing the degree of influence of human capital on achieving organizational readiness and also knowing what are the organizational benefits resulting from human capital and whether this has a direct or indirect impact on building organizational readiness. The importance of the research was to address a problem that most people face. Organizations in general, and Central Technical University in particular, which is represented by the rapid change in the environmental requirements associated with them, which lies in the need for continuous change to build organizational readiness that seeks to achieve the organizations’ requirements and needs. The researchers utilized a descriptive-analytical method, focusing on a sample of administrative leaders from Middle Technical University. They also utilized a survey form to gather data, distributing a total of 310 forms and receiving back 296. The collected data underwent testing through statistical programs such as EXCEL and SPSS v.23. There are many results, most notably the existence of a significant relationship between human capital with its dimensions and organizational readiness, and that the dimensions of the human capital variable are available at a good level, especially in the skills and capabilities dimension. However, they need more focus, especially in terms of providing training programs capable of addressing the problems that exist to enable them. To make appropriate decisions based on sound scientific foundations.Type of paper:- Research paperThe study seeks to assess how human capital, encompassing aspects like knowledge, skills, experience, and abilities, impacts the attainment of organizational readiness across cognitive, emotional, and behavioral dimensions at Central Technical University. The problem of the study begins by addressing the basic question of revealing the degree of influence of human capital on achieving organizational readiness and also knowing what are the organizational benefits resulting from human capital and whether this has a direct or indirect impact on building organizational readiness. The importance of the research was to address a problem that most people face. Organizations in general, and Central Technical University in particular, which is represented by the rapid change in the environmental requirements associated with them, which lies in the need for continuous change to build organizational readiness that seeks to achieve the organizations’ requirements and needs. The researchers utilized a descriptive-analytical method, focusing on a sample of administrative leaders from Middle Technical University. They also utilized a survey form to gather data, distributing a total of 310 forms and receiving back 296. The collected data underwent testing through statistical programs such as EXCEL and SPSS v.23. There are many results, most notably the existence of a significant relationship between human capital with its dimensions and organizational readiness, and that the dimensions of the human capital variable are available at a good level, especially in the skills and capabilities dimension. However, they need more focus, especially in terms of providing training programs capable of addressing the problems that exist to enable them. To make appropriate decisions based on sound scientific foundations.Type of paper:- Research paper